2012
DOI: 10.1177/1076029612459675
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Neutrophil to Lymphocyte Ratio With the Presence and Severity of Metabolic Syndrome

Abstract: The present study indicated a significant correlation between the criteria of MS and inflammation on the basis of NLR. Furthermore, there an increase in NLR as the severity of MS increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
120
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(146 citation statements)
references
References 19 publications
5
120
1
9
Order By: Relevance
“…Recently, the N/L ratio has proven a cost-effective, pragmatic predictive and prognostic tool in a wide array of diseases involving inflammation, e.g. cardiovascular disease, psoriasis, metabolic syndrome, and certain cancers [15,36,37,38,39,40]. Our study found HS associated with higher N/L ratios independently of smoking (a confounder).…”
Section: Discussionmentioning
confidence: 48%
“…Recently, the N/L ratio has proven a cost-effective, pragmatic predictive and prognostic tool in a wide array of diseases involving inflammation, e.g. cardiovascular disease, psoriasis, metabolic syndrome, and certain cancers [15,36,37,38,39,40]. Our study found HS associated with higher N/L ratios independently of smoking (a confounder).…”
Section: Discussionmentioning
confidence: 48%
“…Psoriasis hastalarında diabetes mellitus, atrial fibrilasyon, hipertansiyon, aterosklerozis, stroke, miyokard enfarktüsü, kardiyovasküler mortalite ve metabolik sendrom oranlarının yüksek olduğu uzun zamandır bilinen bir gerçektir [2][3][4][5][6][7] . Son yıllarda nötrofil ve trombosit sayısının lenfosit sayısına (N/L ve T/L oranı) oranının sistemik inflamasyonun bir göstergesi olabileceği ve birçok kardiyovasküler hastalık, maliniteler ve kronik inflamatuvar hastalıklarda prognoz ile ilişkili olduğu gösterilmiştir.…”
Section: Introductionunclassified
“…Son yıllarda nötrofil ve trombosit sayısının lenfosit sayısına (N/L ve T/L oranı) oranının sistemik inflamasyonun bir göstergesi olabileceği ve birçok kardiyovasküler hastalık, maliniteler ve kronik inflamatuvar hastalıklarda prognoz ile ilişkili olduğu gösterilmiştir. Aynı zamanda N/L ve T/L oranlarının eritrosit sedimentasyon hızı (ESH), C-reaktif protein (CRP) ve psoriasis patogenezinde de önemli rol oynayan interlökin-6 (IL-6) ve tümör nekrozis faktör-alfa (TNF-alfa) değerleriyle ilişki gösterdiği tespit edilmiştir [7][8][9][10] . Diğer inflamatuvar hücrelerle beraber trombositlerin de psoriasis patogenezinde rol oynadığı ve aktive olmuş trombositlerin deriye lökosit göçünü arttırıp deride inflamatuvar sitokinlerin salınımını arttırdığı düşünülmektedir 11 .…”
Section: Introductionunclassified
“…In recent years, N/L ratio has been proposed as a surrogate marker for endothelial dysfunction and inflammation in distinct populations and has prognostic and predictive values. 4,5 Although white blood cells are in normal range, subtypes of white blood cells may predict cardiovascular mortality. However, sometimes acute conditions like bacterial or viral infections or drug treatments might affect the neutrophil and lymphocyte counts, and so the ratio of these 2 parameters might be changed.…”
mentioning
confidence: 99%